Bioactive compound C498-0670 alleviates LPS-induced sepsis via JAK/STAT and NFκB signaling pathways - Xu, Jing; Zhang, Xinxin; Zhou, Mingming; Lu, Peizhe; Xu, Yuting; Wu, Lihong; Zhang, Qianyue; Wu, Zhihua; Xu, Xiaoyu; Shi, Pengfei; Wei, Qingda; Li, Xiaoyu; et al. (Frontiers in Immunology, 2023)
The JAK/STAT and NFκB signaling pathways are two major inflammatory signaling pathways that are usually activated simultaneously in the body’s inflammatory response to bacterial or viral infections. Hyperactivation of these two prominent signaling pathways is associated with various immune-related diseases and mortality, pointing to an urgent need for drug development targeting JAK/STAT and/or NFκB signaling. In this study, we screened 18,840 compounds using our well-established dual STAT-NFκB driven luciferase reporter based high-throughput screening system and identified a bioactive compound C498-0670, which inhibits both JAK/STAT and NFκB signaling. C498-0670 inhibits the activation of STATs and p-IKKα/β in both the immortalized cell lines and primary peritoneal macrophages, while suppressing the expression of LPS induced inflammatory mediators in vitro. In addition, the overall anti-inflammatory effects of C498-0670 were thoroughly investigated using transcriptome sequencing and bioinformatics approaches. C498-0670 was predicted to alleviate sepsis/septic shock by disease/function analysis using IPA software, which was further verified in the LPS-induced mouse sepsis model in vivo. C498 reduced LPS-induced hepatic and renal damages, myeloid cell infiltration, and pro-inflammatory cytokine and chemokine production in vivo. Furthermore, the SPR-HPLC-MS-based target fishing approach was used to identify the putative drug targets, and the high affinities of JAK2 (JAK/STAT signaling), NFKBIA (NFκB signaling), and IL-1β, NLRP1b (inflammasome signaling) for C498-0670 were verified by molecular docking approach. These results suggest that C498-0670 can be used as a dual-target inhibitor of JAK/STAT and NFκB signaling pathways for the treatment of various inflammatory diseases as a dual-target inhibitor of JAK/STAT and NFκB signaling pathways, especially septic shock.